Mechanical effects of high density polyethylene Dynamic Compression Plate hole inserts on bone-plate constructs - Sullivan, E. K.; Nunamaker, D. M.; Richardson, D. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
This study was conducted in order to investigate the mechanical effects of high density polyethylene screw hole inserts in 4.5 mm Dynamic Compression Plate (DCP) – synthetic bone constructs. A mid-shaft ‘osteotomy’ was created in synthetic bone cylinders. The bisecting ‘osteotomy’ was reduced using six-hole broad DCPs and 4.5 mm cortical bone screws. The screws adjacent to the ‘osteotomy’ were placed using a loadguide. The remaining screws were placed in neutral position. High density polyethylene DCP screw hole inserts were incorporated with each screw in neutral position, in the experimental group. The bone plate constructs were tested in four point cyclical bending with the plates loaded at 2,000 Newtons, for a total of 6,000 cycles. Osteotomy gap was measured at 3,000 and 6,000 cycles. Screw head deflection adjacent to the osteotomy was measured. Kruskal-Wallis non-parametric testing was used for statistical comparisons. There was significantly less gapping at the osteotomy site in the treatment group after 3,000 cycles (0.49 +/- 0.18 mm [control] vs. 0.06 +/- 0.14 mm [treated], P=0.02) and 6,000 cycles (0.6 +/- 0.18 mm [control] vs. 0.1 +/- 0.22 mm [treated], P=0.02). The screws adjacent to the gap were significantly more deformed in the control group than those in the treated constructs (3.63 +/- 1.81 [control] vs. 1.06 +/- 1.55 [treated], P=0.0002). The polyethylene inserts improved the interface between bone plate and screw head, resulting in decreased relative movement of the implant and bone. The polyethylene inserts also resulted in less bending of the loaded screws.
Keywords: Hdpe inserts; bone construct; cyclical fatigue